A Chinese survey on clinical practice in hyperthyroidism management: comparison with recent studies and guidelines. Issue 9 (8th September 2021) - Wang, Xichang; Teng, Xiaochun; Li, Chenyan; Li, Yushu; Li, Jing; Teng, Weiping; Shan, Zhongyan; Lai, Yaxin
Abstract : Objective: To conduct a questionnaire survey of the current clinical practice for overt hyperthyroidism in China. Methods: An online questionnaire survey was conducted in July 2020. The two questionnaires covered 35 and 8 questions about non-pregnancy and pregnancy clinical practice for overt hyperthyroidism, respectively. Results: One thousand, two hundred fifty-six physicians participated. Chief physicians and associate chief physicians accounted for 58.6% of the participants. Approximately 95.2% of the respondents chose the thyrotropin receptor antibody (TRAb) test to clarify the etiology of thyrotoxicosis, while only 27.0% of them chose radioactive iodine uptake (RAIU). In terms of treatment for non-pregnant patients, anti-thyroid drugs (ATDs) were the first choice, and most of the clinicians chose methimazole. Compared with clinicians in recent studies, Chinese physicians used serum TRAb to diagnose Graves' disease more commonly, and there were obviously more physicians preferring ATDs. For maternal hyperthyroidism, most physicians preferred propylthiouracil administration before or during the first trimester, which is consistent with the 2016 American Thyroid Association (ATA) guidelines. In terms of the initial ATD dose, monitoring the treatment process, indications for ATD withdrawal and treatment of special cases, the preferences of Chinese physicians were generally consistent with the guidelines. Conclusion: Chinese physicians can generally follow the ATA guidelines for the diagnosis and treatment of hyperthyroidism. Moreover, there are small differences from foreign studies or the guidelines with respect to particular problems. These findings provide evidence for future clinical research in China.